2017
DOI: 10.3390/ijerph14050529
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Health Benefits and Willingness to Pay for Parks by Park Users: Quantitative and Qualitative Research

Abstract: Whilst a growing body of evidence demonstrates people derive a range of health and wellbeing benefits from visiting parks, only a limited number of attempts have been made to provide a complementary economic assessment of parks. The aim of this exploratory study was to directly estimate the perceived health and wellbeing benefits attained from parks and the economic value assigned to parks by park users in Victoria, Australia. The research employed a mixed methods approach (survey and interviews) to collect pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 35 publications
2
12
0
1
Order By: Relevance
“…Studies have also suggested that the ideal distance is within 300-400 m since longer distance shows rapid decline in use [56]. Studies have also shown that residents' value greatly and are even willing to pay for having green spaces that are pleasant and easily accessible in their neighbourhoods [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also suggested that the ideal distance is within 300-400 m since longer distance shows rapid decline in use [56]. Studies have also shown that residents' value greatly and are even willing to pay for having green spaces that are pleasant and easily accessible in their neighbourhoods [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Those individuals with very good access to large, attractive, public open spaces were 50% more likely to achieve high levels of walking [ 12 ], and, in another study, the majority of park users engaged in moderate to vigorous physical activity [ 13 ]. Many benefits can be obtained by users of parks, but physical health benefits were found to be the main ones [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, urban parks offer a wide range of benefits, which are physical, psychological, aesthetic, environmental, economic, social, cultural, historical, recreational, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ], and pursue different core values according to visitors’ perceptions [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that people with higher perceived value have higher rates of satisfaction and intention to revisit [ 17 , 18 ]. Thus, the perceived value has a positive effect on the behavior of users [ 5 ]. As services and activities in parks have become more diverse, the values of parks have also become more diverse.…”
Section: Introductionmentioning
confidence: 99%